ANIMATION INTRODUCTION OF PROFILE OF SMK NEGERI 5 JAYAPURA USING MULTIMEDIA ANIMATION COMPUTACION METHOD - Mayor M. H. Manurung; Halomoan Edy Manurung; Kostantina Wandamani (Universitas Medan Area, 2022)
Advances in science and technology can help an institution to support information and promotion, such as creating school profile recognition animations. Sala one vocational secondary in Papua, SMK Negeri 5 Jayapura at this time for the process of introducing school profiles using a website in the form of text so that it would be better if using multimedia components such as animation to clarify school profiles. The purpose of this research is to design animation to help promote SMK Negeri 5 Jayapura to the community to help the school to be able to provide better promotion and service to the community. This animation was created by the multimedia development life cycle (MDLC) development model of Luther Sutopo's multimedia development model which consists of six stages namely Concept, Design, Material Collection, Manufacturing, Testing and Distribution. The software used in the animation process is Blender V 2.79b, Photoshop CS5 and Adobe Audition CS6. The results of the study in the form of animated videos are 6 minutes long and not interactive. The profile creation of SMK Negeri 5 Jayapura has been successfully built to help the school to provide information about SMK Negeri 5 Jayapura, especially the introduction of school profiles to the public.